2023
DOI: 10.1002/smll.202301815
|View full text |Cite
|
Sign up to set email alerts
|

Review of Design Routines of MXene Materials for Magnesium‐Ion Energy Storage Device

Abstract: Renewable energy storage using electrochemical storage devices is extensively used in various field applications. High‐power density supercapacitors and high‐energy density rechargeable batteries are some of the most effective devices, while lithium‐ion batteries (LIBs) are the most common. Due to the scarcity of Li resources and serious safety concerns during the construction of LIBs, development of safer and cheaper technologies with high performance is warranted. Magnesium is one of the most abundant and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 201 publications
0
8
0
Order By: Relevance
“…Nevertheless, the peaks located at 777.7 eV were attributed to CoSe bonds, two satellite peaks were obtained at 778.5 and 783.15 eV, and a distinct peak corresponding to Fe−Co bonds at 779.7 eV was also deconvolved. 21,31 The high-resolution Fe 2p spectra showed that the binding energy of Fe 2p 3/2 was deconvoluted into two peaks at approximately 706.1 and 707.7 eV, matching the presence of FeSe and Fe−O bonds, respectively (Figure 3d). The deconvolution at 713.2 eV was a companion peak.…”
Section: Resultsmentioning
confidence: 97%
“…Nevertheless, the peaks located at 777.7 eV were attributed to CoSe bonds, two satellite peaks were obtained at 778.5 and 783.15 eV, and a distinct peak corresponding to Fe−Co bonds at 779.7 eV was also deconvolved. 21,31 The high-resolution Fe 2p spectra showed that the binding energy of Fe 2p 3/2 was deconvoluted into two peaks at approximately 706.1 and 707.7 eV, matching the presence of FeSe and Fe−O bonds, respectively (Figure 3d). The deconvolution at 713.2 eV was a companion peak.…”
Section: Resultsmentioning
confidence: 97%
“…20,21 Ti 3 C 2 T x MXene with metallic conductivity, surface hydrophilicity, and a layered microstructure is the most studied MXene and is produced by selective etching of Al atoms from the Ti 3 AlC 2 phases. 22 The surface functional groups (−F, −O, and −OH terminal groups) introduced during etching and delamination make Ti 3 C 2 T x MXene easily dispersible in aqueous solutions and allow Ti 3 C 2 T x MXene to be reassembled with other 2D materials using solution processing techniques. 23 Hence, the metallic conductivity coupled with the superior solution processing capability renders MnO 2 /MXene superlattice endows more active sites, faster electron/ion transports, and fewer structural stresses during the charge/discharge process, which can effectively improve the specific capacity, rate performance, and cycling stability.…”
Section: Introductionmentioning
confidence: 99%
“…MXenes, a rapidly growing family of 2D transition metal carbides, nitrides, and carbonitrides, have shown great potential as electrode materials for electrochemical energy storage devices. , Ti 3 C 2 T x MXene with metallic conductivity, surface hydrophilicity, and a layered microstructure is the most studied MXene and is produced by selective etching of Al atoms from the Ti 3 AlC 2 phases . The surface functional groups (−F, −O, and −OH terminal groups) introduced during etching and delamination make Ti 3 C 2 T x MXene easily dispersible in aqueous solutions and allow Ti 3 C 2 T x MXene to be reassembled with other 2D materials using solution processing techniques .…”
Section: Introductionmentioning
confidence: 99%
“…MXene, a 2D layered material, has numerous functional groups, large surface area, and good electrical conductivity. MXene is also a typical ion-insertion/extraction material, which is thought to be a potential material for metal-ion batteries, especially for LIBs, potassium-ion batteries, sodium-ion batteries, or other devices. MXene is a typical layered material composed of transition metal carbides, nitrides, or carbonitrides.…”
Section: Introductionmentioning
confidence: 99%